Islamic Banking Financing Problems In Financing Small And Medium Business In Muamalat Bank Pekanbaru - Joni Hendra; Saparuddin Siregar; Isnaini Harahap; M, Ridwan (Proceeding International Seminar of Islamic Studies, 2019)
This study aims to look at the financing problems and solutions by Islamic Banks to umkm. This research uses qualitative methods and empirical data that can be accessed through OJK or Muamalat bank. Data collection techniques with questionnaire instruments, interviews and direct observation. The object of the research is the perpetrators of umkm in pekanbaru,Riau who are financing customers of Muamalat pekanbaru